Child Protection in the Quran and Hadith: A Thematic Study - Sudarto Sudarto; Kamsi Kamsi; Agus Moh. Najib (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
It’s already been widespread in society concerning the attention of parental rights and their warning against the iniquity to parents, since eventhough there has been commands and encouragement in the Qur’an and the Sunnah, yet they ignore the child rights and protection for him, as if the Qur’an and the Sunnah do not say anything about it. I choose this topic in order to explain about the concern of Qur’an and Sunnah for the child rights. By Using analytic descriptive approach, this study describes child protection  as found in the Qur’an and the Sunnah by means of searching and collecting the Qur’anic verses and Hadist along with the explanation from the commentary books and hadist. The most significance finding in this study is that the attention of Qur’an and Sunnah towards a child begins his birth, by attention to his life, health, line of descent (nasab), and his right for a better life, both when the child is in normal condition or any other specific conditions like a neglected child, an orphan, a disabled child, a child of divorced parents, a victim of war or natural disaster